Development of Risk Management Information System (SIMRISK) for Prevention and Monitoring of Work Safety in Hospital - Rivaldo Oryon Papilaya; Farid Agushybana; Daru Lestantyo (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
Risk management in hospitals must be implemented to minimize risks that threaten the occupational safety and health of hospital human resources, patients, patient companions and hospital visitors, Hospital management has difficulty in collecting information, delays in reporting, inaccurate and incomplete data, difficulty storing data, difficulty in accessing data and manual reporting and recording are some of the problems in the current risk management information system. The research objective is to develop a risk management information system to assist in reporting and recording risk management, work accidents, hazardous and toxic material inventory and occupational disease. The research method is qualitative with a research and development design, the information system development method uses the waterfall method with the stage needs analysis, system design, implementation system and verification system. the results of this study found that there are problems in collecting, tracking, analyzing and following up on decision making. Needs analysis to development of risk management information system with features that facilitate data input, speed up the report process start with the flow of occupational health safety responsible officer to making reports and verified by doctors and occupational health and safety committees, producing output risk management reports, work accident reports, hazardous and materials inventory reports and occupational illness reports. The conclusion of this study is that risk management information system has a positive impact on data processing related to safety and health so that the data is available to be used as a basis for decision making and determining OHS priorities in hospitals Keyword: Accident, Illness, Hazardous, Hospital, Toxic material